Higgsov bozon - Podobnik, Tomaž (Obzornik za matematiko in fiziko, 2014)
The Standard Model is a theory of the electroweak and strong interactions, mediating the dynamics of the known subatomic particles. According to the Model, the mediators ?$W^+$?, ?$W^-$? and ?$Z^0$? of the weak interactions gain mass by the mechanism of spontaneous symmetry breaking - by interaction with the Higgs field. The mechanism can be illustrated by simple allegories. Apart from explaining the mass of ?$W^±$? and ?$Z^0$?, the hypothesis of spontaneous symmetry breaking predicts existence of a condensate of the Higgs field, the so-called Higgs boson. In 2012, the ATLAS and CMS experiments at the Large Hadron Collider at the European Organization for Nuclear Research CERN reported independently that they found a new particle with properties as expected for the Higgs boson. This is a strong evidence for the hypothesis of spontaneous symmetry breaking, and two of its authors, François Englert and Peter Higgs, were awarded the Nobel Prize in Physics for 2013.
Keywords: fizika osnovnih delcev; zgradba atomov; standardni model; šibka sila; veliki hadronski trkalnik